Donald Duck and Edward Elgar: English March in Disney Animation - Haiduk, Maryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. The interdisciplinary approach is one of the advanced methods of studying artistic phenomena in the modern science of humanities. It is especially relevant for the study of the compositions of E. Elgar, as his orchestral music has taken the place of a kind of migratory content in modern culture, which is increasingly presented not in academic concerts, but in interspecific formats of mass cultural affiliation: ceremonial events, cinematic soundtracks, different shows, etc. Scientific consideration of the process of this functional transformation of E. Elgar’s works and the nature of the interaction of his music with the visual range is a perspective and creative vector of musicology. The scientific novelty of the study. For the first time the principles of the interrelation of “Pomp and Circumstance marches” with the eponymous episode “Fantasies 2000” are described at the historical-chronological, compositional, imaginative, dramaturgical as well as intra-thematic levels. A new perspective on the artistic and genre content of E. Elgar’s marches (which are the original cultural component of the modern multimedia space) is proposed and argued. The main objective(s) of the study is to reveal the nature of the interaction of music and animation on the example of the episode about Noah’s Ark from “Fantasy 2000” with Donald Duck in the lead role and the soundtrack based on “Pomp and Circumstance marches” by Edward Elgar. The methodology is based on the principles of interdisciplinary research and concentrates on the interaction of two types of art — animation and music. The biographical-historical method, genre, and thematic methods of music analysis are used. The approach to animation is a study of the artistic features of the character, analysis of the technical features of his drawing, and characterization of the principles of visual composition and dramaturgy. Results of the study. Characteristics of Donald Duck as the main hero of the episode about Noah’s Ark from the film “Fantasy 2000” is described. In parallel, the artistic portrait of Edward Elgar as the creator of “Pomp and Circumstance marches” (which became the basis for the soundtrack of this episode) was studied. The general structure and artistic material of these works of art are analyzed. The nature of the interaction between the visual component of the animation and the thematic complex of the Elgar’s cycle of marches is studied. The following principles of interaction of music and animation are singled out and argued: affinity of forms; the relationship between mosaicism and integrity; monothematism as a structural and compositional basis of the material organization; figurative and emotional flexibility as a dramaturgical basis for development; quoting a concert ritual within the cinematic genre; features of humor; imaginational and dramaturgical parallelism. The significance of the research lies in the expansion of the array of scientific intermedia works devoted to the connections between the music and animation arts. The article enriches the panorama of analytical research on the work of E. Elgar as part of English orchestral modernism.